Perception of Facial Attractiveness Among Orthodontists and Laypersons in Subjects With Canted Occlusal Plane and Chin Deviation. - Masood, Zahra; Maaz, Muhammad; Kanwal, Leelan; Fida, Mubassar; Sukhia, Rashna Hoshang (Journal of Esthetic & Restorative Dentistry, 2025)
Introduction: Surgical correction and orthodontic intervention are considered the ideal approach for patients with chin deviation, yet many opt for non‐surgical alternatives. This study aims to evaluate the acceptable range of occlusal plane cant in cases of chin deviation and assess the perception of different raters. Materials and Methods: A cross‐sectional study was conducted at a tertiary care hospital, involving frontal photographs of adult male and female subjects. Two groups of raters were engaged to assess these modified photographs using a numeric rating scale. An Independent t‐test was utilized to compare the perception between the two groups of raters, and for the comparison of esthetic scores related to occlusal plane cant toward and away from chin deviation, paired t‐test was employed. A generalized linear model was utilized to compare the perception between the two group of raters, esthetic scores toward and away from chin deviation and to assess the factors associated with male and female facial attractiveness scores. Results: A statistically significant distinction was identified in the evaluation of facial esthetics between orthodontists and laypersons (p ≤ 0.05). Orthodontists showed increased sensitivity to mild facial asymmetries, with esthetic scores beginning to diverge at cant angles as low as 2°. Furthermore, a significant difference in esthetic scores was observed specifically at 4°, 6°, and 8° of occlusal cant away from chin deviation in both male and female subjects (p ≤ 0.05). Conclusions: Orthodontists were more critical compared to laypersons in diagnosing minor asymmetries. Female gender received higher esthetic scores from laypersons compared to orthodontists. Both orthodontists and laypersons rated the cant away from chin deviation as more esthetically pleasing. Clinical Significance: These findings suggest that minor occlusal cant may be esthetically acceptable, potentially minimizing the need for major interventions while aiding clinicians in patient management.